Comparative historical development of Prekmurje spelling - Előd Dudás (Jezikoslovni zapiski, 2015)
This article presents the historical development of Prekmurje spelling from its beginnings to the First World War. It focuses on graphemes not in the Latin alphabet whose representation posed a major problem for writers. In addition, it discusses the origin of individual graphemes and their connection with Hungarian, German, and Czech spelling. The article concludes with a table of the spelling conventions used in forty-one Prekmurje books and newspapers.